THU0037 Personality Traits in Patients with Rheumatoid Arthritis: An Unrecognized Predictor of Mortality. (15th July 2016) - Crowson, A.D.; Colligan, R.C.; Matteson, E.L.; Davis, J.M.; Crowson, C.S.
Abstract : Background: Psychosocial factors, such as pessimistic explanatory style, are shown to affect the course of treatments in many illnesses (Cardiovascular diseases, lung cancer, Parkinson's disease). Little is known about how pessimistic explanatory style affects rheumatoid arthritis (RA). Objectives: The aim of this study was to determine if pessimistic explanatory style altered the risk for and mortality rates of RA patients. Methods: The study used a subset of patients who completed the Minnesota Multiphasic Personality Inventory (MMPI) from among a population-based cohort with incident RA in 1955–2007 and an age- and sex-matched non-RA comparison cohort. Only patients who were ≥18 and fulfilled the American College of Rheumatology (ACR) 1987 criteria for RA were included. Pessimistic explanatory style was measured using the Optimism-Pessimism scale (PSM≥60). Logistic regression and Cox models were used to examine the associations between pessimistic explanatory style and development of RA or mortality rates. Results: There were 148 RA and 135 non-RA subjects who completed the MMPI. Pessimistic explanatory style was associated with development of rheumatoid factor positive (RF+) RA (odds ratio [OR]:1.74; 95% confidence interval [CI]: 0.99–3.04; p=0.053 adjusted for age, sex, smoking and obesity). Among patients with RA, mortality risk adjusted for age, sex, year, smoking, and Charlson Comorbidity Index was increased with a pessimistic explanatory style (hazard ratio [HR]:2.88; 95%CI: 1.02–8.14), similar to mortality risk in RF+ RA patients (HR:2.28; 95%CI:1.10–4.73). A significant interaction between RF+ and pessimistic explanatory style indicated that having both did not confer an additive effect (p=0.037). The 10 year survival percentages were highest for those with RF-RA who were not pessimistic (93%) and were similar for patients with RF+RA who were not pessimistic (73%), those with RF-RA who were pessimistic (77%), and those who were both RF+RA and pessimistic (84%). This association did not change after adjusting for the MMPI depression scale or a history of depression prior to diagnosis of RA. Conclusions: Having a pessimistic explanatory style was associated with an increased risk of developing RA and increased mortality rate in patients with RA. In these patients, the effects of RF+ and pessimistic style were not additive. The patient's psychological state strongly affects treatment decisions and outcomes and can inform about the usefulness of mindful interventions (e.g. cognitive behavioral therapy). Understanding the explanatory style is an important step in the holistic management of disease and a vital component of integrated care. Disclosure of Interest: None declared